2015
DOI: 10.1039/c5nr01088h
|View full text |Cite
|
Sign up to set email alerts
|

Broadband optical limiting response of a graphene–PbS nanohybrid

Abstract: Graphene-based materials have shown promising nonlinear optical properties in the visible range. To extend their nonlinear optical response to the near infrared (NIR) region, we prepared a new nanohybrid consisting of uniform PbS quantum dots (QDs) attached on the reduced graphene oxide, named rGO-PbS, via a facile, low-cost, and phosphine-free method. The rGO-PbS nanohybrid exhibited superior optical limiting properties to either graphene oxide or PbS QDs upon both 532 nm and 1064 nm excitation in the nanosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…It showed that β for 0.25 g TBT was 39 times larger than that of GO, and β for 0.1 g P25 was 24 times larger than that of GO. The result confirmed that the TiO 2 addition to GO enhanced nonlinear absorption [11]. Based on the above results, the TiO 2 /rGO composites exhibited better optical limiting performances than their individual components, probably corresponding to the reduction from GO to rGO and synergetic effects.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…It showed that β for 0.25 g TBT was 39 times larger than that of GO, and β for 0.1 g P25 was 24 times larger than that of GO. The result confirmed that the TiO 2 addition to GO enhanced nonlinear absorption [11]. Based on the above results, the TiO 2 /rGO composites exhibited better optical limiting performances than their individual components, probably corresponding to the reduction from GO to rGO and synergetic effects.…”
Section: Resultssupporting
confidence: 70%
“…During the test process, the detectors collected and recorded the incident laser energy and the transmitted laser energy, and transmittance was obtained when the sample was translated through the focal plane of a tightly focused beam. The transmittance of samples can be regarded as a function of the displacement distance (Z) [11]. When the material was translated close to the focus of the beam, the intensity of the incident beam increased, and the materials exhibited optical limiting effects as a result of its nonlinear optical properties, such as the decline of the transmittance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] PbS QDs with a size greater than 4.74 nm exhibit a cuboctahedron shape with truncated (100) facets (Figure 1c). [50] QDs with tunable sizes offer tunable bandgaps from 0.7 to 2.1 eV, exhibiting strong absorption for both visible and near-infrared (NIR) light. [59][60][61][62] Moreover, PbX QDs possess a large Bohr exciton radius, enabling efficient and balanced charge transport, particularly suitable for PV applications.…”
Section: Introductionmentioning
confidence: 99%
“…The optical limiting in carbon-based materials, in particular, in graphene and in its derivatives, has been extensively investigated in the last years [14][15][16][17]. The optical limiting functionality of these materials, as suspension, film or bulk, has been mainly studied for visible and near-infrared nanosecond and picosecond laser pulses (for wavelengths shorter than 1100 nm) [18][19][20][21] and, to a lesser extent, for femtosecond laser pulses (mostly at 800 nm wavelength) [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%